MENINGKATKAN KEMAMPUAN MEMBACA KATA BAGI ANAK TUNAGRAHITA RINGAN KELAS D3/C MELALUI MEDIA KARTU SUKU KATA. (PENELITIAN TINDAKAN KELAS DI SLB AL HIDAYAH MAEK PAYAKUMBUH) - Yelni Eva Roza (Jurnal Penelitian Pendidikan Khusus, 2012)
The background of this research came from the discovery of a mild grade III Tunagrahita students who have problems reading the syllables, in which the child difficult to distinguish between the letter [b], [d], and [p]. The purpose of this penilitian is improving reading skills for children Tunagrahita said light [X and Y] in the base class III in SLB maek Hidayah Al-Kab. Fifty Cities. This type of study is classroom action research (classroom action research) is conducted in collaboration with colleagues. The study was conducted three cycles. I cycle of meetings held four times in the learning process that starts from listening to the teacher about the use of media, said the letter clearly distinguish the letters in a word, syllable reading, read words and complete the exercise. Based on the average value obtained by students at the end of the cycle I can see that X before given the action obtain a value of 20% and after a given action I get the value of 60%. Y before the action was given a value of 10% and after a given action I get the value of 60%. Whereas in the second cycle performed four times in the learning process through the use of media to read the beginning of the syllable card. Where X is the cycle of 60% grades II and Y gets value of 60%. Proceed to the third cycle, the cycle was conducted six sessions. X get Y value of 80% and 70% get results.